Alpha radioactive aerosols behavior in the ground atmosphere; European Aerosol Conference, EAC 2013, Prague, Czech Republic, 1-6 September 2013 - Yakovleva V. S. Valentina Stanislavovna; Cherepnev M. S. Maksim Sviatoslavovich; Ипполитов И. И. Иван Иванович; Нагорский П. М. Петр Михайлович; Smirnov S. V. Sergey Vasiljevich; Vukolov A. V. Artem Vladimirovich (2013, 2013)
Title screen